Energy efficiency in data centers and clouds - Hurson, Ali; Sarbazi-Azad, Hamid (Advances in computers ;, 2016)
Advances in Computers carries on a tradition of excellence, presenting detailed coverage of innovations in computer hardware, software, theory, design, and applications. The book provides contributors with a medium in which they can explore their subjects in greater depth and breadth than journal articles typically allow. The articles included in this book will become standard references, with lasting value in this rapidly expanding field.